Strike Bulletin No. 5, Merseyside Council of Action, 10 May 1926 (Liverpool)
1926-05-10 "Strike Bulletin No. 5, Merseyside Council of Action, 10 May 1926" [g0061001.jpg], 10 May 1926, Merseyside Council of Action Local Organisation